Strangulated sigmoid volvulus with severe hypothyroidism: A disastrous combination, our experience - Praveen, CR; Patowary, BN; Agarwal, A; Kumar, S; Karmacharya, A; Shrestha, P (Journal of College of Medical Sciences-Nepal, 2012)
Both sigmoid volvulus and hypothyroidism, can individually have serious repercussions in terms of morbidity and mortality. Even worst, is a combination of these two clinical entities. We report a case of this lethal combination, which had gone into myxedema coma after emergency surgery for strangulated sigmoid volvulus. Patient could be saved because of early identification and meticulous management. It is suggested to have high index of suspicion of hypothyroidism in patients of volvulus. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5974 JCMSN 2011; 7(1): 52-56